Pengembangan Media Pembelajaran Matematika Berbasis Macromedia Flash pada materi koordinat kartesius kelas VIII SMP - Muhammad Agung Alghifaari; Nani Kurniati; Wahidaturrahmi; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this research are to develop macromedia flash-based mathematics learning media for cartesian coordinate material for class VIII SMPN 19 Mataram. Macromedia flash-based learning media is an audio-visual media presented in the form of software consisting of basic competencies, learning objectives, materials and quizzes. This development aims to overcome the weaknesses in the learning process that have occurred due to the lack of use of media in classroom, besides that it can also assist students in learning the concept of cartesian coordinates, especially in visualizing the objects in the material. The research methodology used in developing this learning media is 4D (Define, Design, Developement, Dissemination). Data collection techniques using interview guidelines and questionnaires. The result of this research is a software product of learning media for cartesian coordinates based on macromedia flash in the CD form. The product has been declared valid with good criteria by 4 validators. Based on the limited trial, it is known that the response of class VIII students of SMPN 19 Mataram that use the macromedia flash-based learning media cartesian coordinate is good.